Law at the Movies: Turning Legal Doctrine into Art. - GOODRICH, PETER (Journal of Law & Society, 2025)
The document titled "Law at the Movies: Turning Legal Doctrine into Art" reviews the work of Stanley Fish, a professor who explores legal doctrine through the lens of film. Fish's analysis focuses on movies like "The Fugitive" and "12 Angry Men" to examine themes of freedom, responsibility, and the conflict between individualism and law. Through his reviews, Fish critiques legal decisions in classic movies and explores the intersection of law and visual media. The document highlights the significance of using movies to teach law, emphasizing the visual transmission of legal concepts and the role of images in jurisprudence.